DISEMINASI DARING PKM-PM AZIMATH ADVENTURE: PENGUATAN LITERASI NUMERASI SISWA SEKOLAH DASAR SEBAGAI FONDASI LITERASI KESEHATAN DAN REGENERASI MAHASISWA BARU - Kusuma, Heri Septya (JURNAL PARADIGMA (PEMBERDAYAAN & PENGABDIAN KEPADA MASYARAKAT), 2025)
Numeracy is a fundamental skill that should be mastered from the elementary school level, serving not only academic purposes but also as a foundation for daily problem-solving and health literacy. However, the 2022 PISA results revealed that Indonesian students’ mathematics performance remains relatively low, underscoring the need for early interventions. Responding to this challenge, the Azimates team developed an innovative learning media, Azimath Adventure, to strengthen the numeracy skills of fifth-grade students at SD Negeri 2 Pangenjurutengah. The program employed a game-based learning approach, enabling students to engage in interactive mathematical activities. Pre-test and post-test results demonstrated improvements in students’ numeracy performance, indicating the effectiveness of this intervention. In addition to the school-based activity, the program incorporated a dissemination session conducted online via Zoom, targeting freshmen students of the 2025 cohort. This dissemination aimed to introduce the fundamental concepts of the Community Service Program (PKM), particularly PKM-PM, while also sharing practical experiences from the Azimath Adventure implementation. The session was structured into presentations, discussions, and interactive Q&A, attended by 53 participants, of which 48 were freshmen. The outcomes highlighted twofold contributions: (1) elementary students benefitted from enhanced numeracy skills as part of their cognitive and health literacy foundation; and (2) freshmen students gained initial understanding of PKM, strengthened motivation to participate in future community service projects, and developed awareness of program management. This integrated activity illustrates how combining school-based interventions with online academic dissemination can provide significant added value for both community partners and student participants. The program also demonstrates alignment with principles of health education (knowledge transfer), health administration (systematic program planning and management), and health research (evaluation and documentation of outcomes for future replication).